Natural enemies of Pentalonia nigronervosa, vector of Banana Bunchy Top Virus - TITI TRICAHYATI; SUPARMAN SUPARMAN; CHANDRA IRSAN (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Tricahyati T, Suparman, Irsan C. 2022. Natural enemies of Pentalonia nigronervosa, vector of Banana Bunchy Top Virus. Biodiversitas 23: 3675-3684. Pentalonia nigronervosa (Coquerel) is an important pest of banana. Instead of sucking liquid from banana phloem, P. nigronervosa also play an important role in transmitting Banana Bunchy Top Virus (BBTV) from infected banana to healthy ones. If efforts are not made to control the aphid, existence of P. nigronervosa can increase in the banana field. The objective of this research was to find out the natural enemies of P. nigronervosa which may play significant role in controlling the aphid naturally. The results showed that natural enemies were in the forms of predator, parasitoid and pathogenic fungi. A total of 22 species of predator belonged to 5 families of insect, namely Coccinellidae, Forficulidae, Chelisochidae, Reduviidae and Syrphidae, and 4 families of Arachnida i.e. Oxyopidae, Araneidae, Salticidae, and Philodromidae. The result exhibited that one parasitoid belonged to family Brachonidae, and one hyper-parasitoid belonged to family Encrytidae. Furthermore, it was also observed that 3 species of entomopathogenic fungi infected aphids. The fungi belonged to genera Aspergillus and Beauveria. Each predator had different predation capacity, the highest was that of Forficula auricularia (23.67 ± 3.05) and Scymnus sp. (23.67 ± 1.52). Parasitoid Lipolexis bengalensis could parasitize P. nigronervosa at relatively high parasitic ability of 4.67 ± 23.65. The finding of various natural enemies of P. nigronervosa in South Sumatra could be considered as an alternative way to control the aphid and reduce the transmission rate of BBTV in the province. The use of natural enemies has no residual effects on the environment and is relatively cheaper compared to other control measurements.